Estimasi Sumberdaya Pit 1 Blok Selatan dengan Metoda Silcular 5015-2019 Daerah Puruk Cahu Kalimantan Tengah - Asep Tri Herdianto; Erwin Wijaya, Andy (Institut Teknologi Nasional Yogyakarta, 2024)
Coal is one of the energy minerals found in Indonesia with significant potential, particularly in Kalimantan. The objective of this research is to calculate a more accurate estimate of reserves in the study area with a thickness range of 1-1.2 meters. The distribution of the seam generally follows a pattern from Northeast to Southwest with a moderate dip angle of 70-80 degrees. Based on SNI 5015-2011, the geological complexity of the study area falls into the â€œComplexâ€ category according to SNI 5015-2019 due to the steep inclination of the rock layers. The estimation of coal resources using the Circular Method, aided by software, yielded the following results: measured coal resources of 1,127,778.23 tons, indicated resources of 2,024,364.08 tons, and inferred resources of 2,948,000.06 tons.